Potensi Kombinasi Adenosine Diphosphate-Ribosylation Like 4c Antisense Oligonuclotide-1316 dengan Polyamidoamine Dendrimer Generasi 4-Anti Surfactant Protein B sebagai Terapi Adenokarsinoma Paru - Adrian Wiryanata Gorintha; Andrea Ivena; Putu Aprilyanti Aristadewi; Agung Wiwiek Indrayani (Jurnal Epidemiologi Kesehatan Komunitas, 2022)
Background: Lung cancer is a disease of the respiratory system that gets special attention because the World Health Organization (WHO) has reported that in 2018, lung cancer was the cancer with the highest number of morbidity and mortality rate in the world. There are several types of lung cancer, one of which is adenocarcinoma, which accounts for about 40% of all lung cancers. In its management, cancer cells often develop resistance to EGFR TKI drugs while Cisplatin and Crizotinib have quite dangerous side effects, namely bradycardia to cardiotoxicity.Methods: The method used is a literature review with literature sources in the form of relevant article from search engine such as Pubmed and Google Scholar that contain keyword “ARL4C ASO-1316”, “lung adenocarcinoma”, “PAMAM Dendrimer Generasi 4” and “anti SFTPB antibody”.Result: The ability of ARL4C ASO-1316 in inhibiting the division and migration of lung adenocarcinoma cells has been proven in vivo and in vitro so that it can provide hope in the form of new modalities in the treatment of lung adenocarcinoma. In addition, the combination with the PAMAM Dendrimer G4-Anti SFTPB carrier can increase the ability to deliver ARL4C ASO-1316 to reach target tissues rapidly and can provide maximum effect in the treatment of lung adenocarcinoma.Conclusion : Adenosine diphosphate-ribosylation like 4c antisense oligonuclotide-1316 with polyamidoamine dendrimer generation 4-anti surfactant protein b should provide novel approaches and new insights for lung adenocarcinoma.